DEVELOPMENT OF SDGs-INTEGRATED CAROUSEL-BASED MICROLEARNING CONTENT FOR ENHANCING STUDENTS' SCIENTIFIC LITERACY SKILLS ON ENVIRONMENTAL POLUUTION - Maisaroh, Tsaniatul; Fida Rachmadiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ low science literacy skills and the importance of integrating the Sustainable Development Goals (SDGs) into the teaching of the environmental pollution subtopic underscore the need for innovative learning media that support 21st-century learning. This study aims to develop SDGs-integrated, carousel-based microlearning content on the environmental pollution subtopic that is valid, practical, and effective for fostering students’ science literacy skills. This development study employed the 4D model (define, design, develop, and disseminate) with a pilot test involving 25 10th-grade students at SMA Negeri 1 Sidayu, Gresik. Research instruments included a validation sheet, a lesson implementation observation sheet, a student response questionnaire, and a science literacy skills test. Data were analyzed using quantitative descriptive methods, while the effectiveness of the media was analyzed using a paired-sample t-test and N-Gain. The results showed that the SDGs-Integrated Carousel-Based Microlearning Content achieved a validity percentage of 98.8%, falling into the “highly valid” category. The practicality of the media was demonstrated by a lesson implementation rate of 96.3% and a student response rate of 98.6%, both of which fell into the “highly practical” category. The effectiveness of the medium was demonstrated by the results of a paired-sample t-test, with a significance value of 0.000 (<0.05) and an N-Gain value of 0.7035, which falls into the high category. Thus, the SDGs-Integrated Carousel-Based Microlearning Content is deemed valid, practical, and effective for developing students’ science literacy skills in the subtopic of environmental pollution.